Incidental finding of tracheobronchial foreign body during double lumen tube placement-lessons learned - Kurnutala, Lakshmi N. (Saudi J Anaesth, 2020)
Tracheobronchial foreign bodies are common in pediatric patients, but also seen in adult patients. Most of these patients present with history of foreign body inhalation, or with the symptoms like cough, respiratory distress. In this paper, we would like to report an incidental finding of a tablet in tracheobronchial tree during double lumen tube placement with fiberoptic bronchoscopy in a middle-aged patient scheduled for right lung decortication for hemothorax. We also learned that delay in removing the tablet would make the removal of foreign body complicated. The patient did not report any history of aspiration or have any signs and symptoms consistent with aspiration. We also discussed the difficult in diagnosing foreign-body aspiration in adults with nonspecific symptoms.